Varicella pneumonia in an immunocompetent child: A case report - Pramodman Singh Yadav; Pratik Adhikari; Narendra Mohan Jha; Shuvam Khadka; Sujan Kafle; Sweta Singh; Suman Subedi; Mukesh Bhatta (IDCases, 2023)
Varicella-zoster virus (VZV) is a type of herpes virus that causes varicella (primary infection) and herpes zoster/shingles (due to reactivation of latent infection). Usually a benign and a self-limited illness, the illness sometimes can result in severe complications in both immunocompetent and immunocompromised persons. Varicella Pneumonia as a complication of herpes zoster is a rare event, with reports primarily concerning immunocompromised individuals. Here we report a 14-year-old female who developed a secondary bacterial infection of the skin lesions and varicella pneumonia associated with VZV infection. The patient presented with multiple painful vesicles that later turned into pustular lesions over the right cheek with erosions and hemorrhagic crusting. Swelling involving the right half of both upper and lower lips was present. She developed a fever, cough, and shortness of breath after two days of the presence of vesico-pustular lesions. A diagnosis of Pneumonia was made based on symptoms of fever and cough and findings on chest x-ray. This case highlights, though rare, varicella pneumonia has a high rate of respiratory failure, but early diagnosis with prompt administration of antiviral medications can improve outcomes.